Legal Protection for Workers from Direct Termination of Employment by Employers: Legal Vagueness and Its Strengthening - Firjatullah, Muhamad Sulthan; Wasis, Wasis; Hidayah, Nur Putri (Universitas Muhammadiyah Malang, 2025)
This research aims to find out how to analyze legal protection for workers against direct termination of employment by employers. The research method used in this research was the normative juridical research method, which used a statutory approach and conceptual approach in assessing legal protection for workers against direct termination of employment by employers. The results of this study conclude that the provisions of Article 52 Paragraphs (2) and (3) of Government Regulation No. 35 Year 2021 do not provide preventive legal protection for workers because they do not provide an opportunity for workers to give their opinions before layoffs are carried out and the provisions of Article 52 Paragraphs (2) and (3) do not prevent layoffs. Article 52 Paragraphs (2) and (3) of Government Regulation No. 35 Year 2021 conflict with Article 52. 35 Year 2021 conflict with Article 28D Paragraph (1) of the 1945 Constitution of the Republic of Indonesia, contradicts the consideration letters c and d of the Manpower Law, contradicts Article 4 letters c and d of the Manpower Law, and contradicts the general explanation of the Manpower Law, the actions categorized as urgent violations in the article are criminal acts, but the article does not regulate the requirement that this urgent violation be proven first through a court decision with permanent legal force so that it has also violated the principle of presumption of innocence.